How well do Croatian learners speak English? - Medved Krajnović, Marta (Array, 2007)
The paper discusses issues related to assessing the speaking skill in English as a foreign language. The paper also presents the process and the results of assessing the speaking skill of a representative sample of Croatian learners of English. Assessment results show that the learners are communicatively competent when speaking English. Although this is the main goal of teaching EFL, the author stresses that in the process of teaching more attention should be given to the accuracy of learners' speach.